Measurement of Company Financial Performance Using Debt to Equity Ratio and Debt to Total Asset Ratio in Mining Companies in Indonesia - Roza, Seflidiana; Arfimasri, Arfimasri; Meilani, Intan (Journal of International Accounting, Taxation and Information Systems, 2025)
This research assesses how debt ratios influence the financial performance of Indonesian coal mining firms by utilizing regression analysis. A sample of 23 coal mining companies listed on the Indonesia Stock Exchange was studied, chosen through purposive sampling from a total of 33 companies between 2020 and 2023. Statistical analysis reveals that Debt to Equity Ratio significantly affects Financial Performance (ROE), demonstrated by a t-test significance value of 0.001 < α 0.05 and t-value of -3.390 > t-table 1.667. Similarly, Debt to Total Asset Ratio shows significant partial impact on ROE, with t-test results indicating significance of 0.005 < α 0.05 and t-value of 2.912 > t-table 1.667. The F-test confirms that both debt ratios simultaneously influence financial performance, showing significance of 0.003 < α 0.05 and f-value of 6.169 > f-table 3.130. The 0.152 R-squared value suggests that 15.2% of the variability in ROE is accounted for by the independent variables, leaving 84.8% of the variability to be influenced by unexamined factors in this research. The findings demonstrate that debt management strategies significantly impact financial performance in the coal mining sector.